Traditions, fundamentality, innovation - A. I. Trubilin (Высшее образование в России)
On the threshold of Kuban State Agrarian University’s anniversary historical aspects oftraining agrarian specialists, lines of university’s activity are considered. Also it is stressed the role of the university in training world level agrarian specialists. The specifics of staff training for working under market conditions is characterized.